A Philological Study of Some Pyu Words through Inscriptions - Mon, Swe Swe (The Journal of International Association of Buddhist Universities (JIABU), 2018)
Regardless of disputes and different opinions of archeologists on historical data of Pyu people and their kingdoms, this paper aims to do a philological study of some of Pyu’s words through its inscriptions. Firstly some Pyu inscriptions will be generally studied to shed light on the Theravā da influence in Pyu Period. Pyu language based on Pāḷi and Sanskrit thus it performs as a bridge between Pāḷi, Sanskrit and Myanmar languages to some extent. Though it is based on Pāḷi and Sanskrit, it does not use the words directly from those languages. Therefore, it can be regarded that the Pyu language is the evolution of Pāḷi and Sanskrit. In the evolution process, words may either slightly or totally change. In this work, the subtle Pyu’s words of consecrated Queen, water, Buddha, well-done/let the goodness be and slave will be philologically studied to prove that they are derived from Pāḷi language.